إشكالية محاسبة الأصول الرقمية وتنمية مهاراتها - خالدي، رشيدة; عزه، الأزهر (University Of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة بالأساس على التعرف على أحد المنتجات الرقمية للاقتصاد الرقمي ألا وهي الأصول الرقمية، والتي تعتبر من بين أهم المنتجات الرقمية التي وجب على المهتمين بالاقتصاد ككل والاقتصاد الرقمي خاصة الالمام بجميع جوانبها، حيث تم من خلال هذه الدراسة الاعتماد على المنهج الوصفي التحليلي من خلال عرض أهم الأدبيات المتعلقة بموضوع الدراسة وتحليل أهم الأساليب المحاسبية المتعلقة بالأصول الرقمية. في الأخير توصلت الدراسة على مجموعة من النتائج من أهمها أن في الاقتصاديات المتقدمة تتم معالجة لأصول الرقمية محاسبيا وفي الغالب كأصول غير ملموسة إلى أن هذا النوع من المعالجات المحاسبية لا يزال يحتاج الكثير من الارشادات والتوجهات بغية توحيد الممارسات المحاسبية. Abstract: This study aims primarily to identify one of the digital products of the digital economy, namely digital assets, which are considered among the most important digital products that those interested in the economy as a whole and the digital economy in particular must be familiar with all aspects of, as this study relied on the descriptive analytical approach by presenting the most important literature related to the subject of the study and analyzing the most important accounting methods related to digital assets. In the end, the study reached a set of results, the most important of which is that in advanced economies, digital assets are treated in accounting and mostly as intangible assets, and that this type of accounting treatment still needs a lot of guidance and directions in order to unify accounting practices.
The problem of digital assets and developing their skills
مداخلة
Keywords: اقتصاد رقمي; منتجات رقمية; أصول رقمية; محاسبة الأصول الرقمية; Digital economy; digital products; digital assets; digital asset accounting